PENDIDIKAN BUDAYA DAN KARAKTER BANGSA PADA PROSES PEMBELAJARAN SENI TARI & DRAMA - Ramlan Ramlan; Jaka Permana (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2016)
Facing the nation issue which is considered associated with the failure of the government in the education sector, on the new Nation Curriculum concept (Kurikulum 2013), there are so many highly thigs containing the character building concept. It became the new challenge for the teachers to quickly change the old mindset that teaching is just to make people smart, but they should give priority to build the students’ characters. The fact from the field is that to change the minset of the teacher is not easy. There are so many researches has been done, that teachers still teaching with old habits or inconventional ways.This is a Research and Development ( R&D ) to character building concept and cultural arts education, especially on dance and drama studies. His research is done towards teachers and elementary students. Through the steps of R&D’s research methods which have olready resulted a Model of Learning Dance and Drama that could be used by the teachers to teach Dance and Drama lesson in school that could help them to build the student’s character. Keyword : Character Building, Dance and Drama LessonKeyword : Character Building, Dance and Drama Lesson